Meningkatkan Hasil Belajar dengan Metode Problem Based Learning pada Materi Perempuan dan Laki-Laki Diciptakan sebagai Citra Allah Fase C Kelas V SD Negeri 071119 Hilisondrekha, Kabupaten Nias Selatan - Petrus Niarman Gee (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve the learning outcomes of Catholic Religious Education and Character Education subjects through the Problem Based Learning (PBL) method for fifth-grade students at SD Negeri 071119 Hilisondrekha during the 2024/2025 academic year. This research is a Classroom Action Research (CAR) conducted in two cycles, with one meeting in each cycle. Each cycle consists of several stages: planning, action implementation, observation, and reflection. The first and second cycles cover the topics of